Ketidakpastian Hukum dalam Transaksi Jasa Titip Luar Negeri Tanpa Kontrak Tertulis dan Peran Contract Drafting sebagai Instrumen Perlindungan Hukum - Putra, Muhamad Ilham Nugraha; Siswana, Rahmania Diva; Silkani, Ni Luh; Rajib, Rayi Kharisma (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The phenomenon of overseas proxy shopping servicesis growing rapidly as part of the digital economy, but the practiceis informal and without written contracts, creating legal uncertaintyfor all parties. Jastip transactions, which are often conducted through social media, rely solely on trust and brief communication, creatingvulnerabilities to fraud, default, non- conforming goods, damage,and issues of responsibility for customs fees and cross- jurisdictional risks. The absence of a contract means that the legal relationship between the jastiper and the consignor lacks a clear structure, making it difficult to determine rights,obligations, and dispute resolution in the event of loss. This articleanalyzes the forms of legal uncertainty in foreign jastip transactionswithout contracts and explains the strategic role of contract drafting as ainstrument of legal protection. Through the preparation of a written contract that includes the identities of the parties, specifications of the goods, risk sharing, costs, delivery mechanisms, refunds, and dispute resolution, contract drafting is able toprovide legal certainty, protect the rights of the parties, minimize the risk ofdisputes, and increase the professionalism of jastip practices. Therefore,the existence of a written contract is not merely a formality, but a fundamental necessityto create safe, transparent, and accountable jastip transactionsin the cross-border digital trade ecosystem